Dynamic coupling across energy forms and hybrid simulation of the multi-energy system - Zhang, Shuqing; Hu, Xianfa; He, Xianggang; Tang, Shaopu; Li, Haibo; Zhang, Donghui (Frontiers in Energy Research, 2023)
A multi-energy (ME) system can coordinate local energy sources and users and optimize the supply of various energy forms, to maximize the comprehensive utilization efficiency of energy. As the scale of the multi-energy system becomes more extensive and the physical connections of different energy forms become diversified, the coupling of various forms of energy becomes closer. Such development has brought significant challenges to safe operations and effective regulation of the system and equipment. However, no efficient and easy-to-use dynamic simulation method is available for multi-energy systems. It has become an urgent problem how to fully use the existing rich models and algorithms of conventional energy systems to construct the dynamic simulations of multi-energy systems. Based on the multi-energy system's structure, components, and model characteristics, this paper studies the mechanism of cross-energy-form dynamic coupling, proposes the critical techniques of multi-energy hybrid simulation and verifies the effectiveness and accuracy of the methods through case tests.